Transformasi Remote Work dalam Era Digital: Literatur Review Mewujudkan Keberlanjutan Kerja - Dewa Putu Yohanes Agata L. Sandopart (Review of Applied Accounting Research (RAAR), 2026)
This study aims to explore the transformation of remote work in the digital era and its impact on work sustainability. Using a thorough literature review approach, the research analyzes the growth trends of remote work from 2020 to 2025. Data collected shows that in 2020, there were 8 publications related to the topic, which increased to 26 in 2022, reflecting growing interest in remote work as digital technology rapidly advanced. Despite this increase in 2022, subsequent data shows fluctuations in the number of publications, with a significant drop in 2026, with only 3 publications recorded. This suggests a shift in focus or a change in the understanding and approaches to remote work. Furthermore, data analysis reveals a sharp decline in certain aspects, such as the impact of technology on productivity and employee well-being. This study also incorporates 110 Scopus Q1 to Q3 articles, providing a comprehensive view of the topic. The research emphasizes the importance of adaptive policies and organizational strategies that support a balance between work flexibility and managerial needs to ensure long-term sustainability.